Communication of middle students from Semarang in adaptation at Telkom University - Daffa Alfiant Putra; Maylanny Christin (Jurnal Mantik, 2023)
Overseas students are a group of students who are not limited by the scope of distance, both in the real sense and in terms of differences in cultural background. They are individuals who are foreign to the cultural environment around the campus. Many overseas students are shocked by the culture when they arrive at Telkom University, especially for new students. This condition is psychologically influenced by the distance from the place of origin and far from relatives and family. This study uses a qualitative descriptive method using an interpretive paradigm. The research subjects consisted of primary subjects consisting of Telkom University students from Semarang and secondary subjects who were additional subjects in the form of prior research or related literature. The results of the study showed that the adaptation process experienced by new students from Semarang was caused by differences in the sweet taste which was very distinctive and dominated in their area of ??origin, while the culinary trend of Sundanese Bandung leaned towards salty taste. Likewise the results formed from the adaptation process for students from Semarang based on the five stages of cultural adaptation, show that the experience of each student at each stage is different then both language, taste of food, city safety, geographical conditions, social styles, and negative thoughts are some variables that cause culture shock. Many challenges are experienced by new students from Semarang themselves. As a result, they must be able to adapt by maintaining good relations with their families, interacting with the surrounding community, both the campus and the boarding house environment, so they can learn and understand the local language, and be open and accept all the differences that occur.